Über erzeugende Funktion der Momente des Zahles der Wiederstellungen im Falle des diskreten Wiederstellungprozesses - Liutikas, V. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Лютикас, О производящей функции моментов числа восстановлений в случае дискретного процесса восстановленияV. Liutikas, Apie atstatymų skaičiaus momentų generuojančią funkciją diskretinio atstatymo proceso atveju